The protective effect of vitamin D on ovarian reserve and anti‐mullerian hormone in patients undergoing chemotherapy for breast cancer, a randomized phase ΙΙ clinical trial - Zahra Dastmardi; Marzieh Lashkari; Arefeh Saeedian; Mahdi Aghili; Sadaf Alipour (Cancer Reports, 2024)
Abstract Background Reduced ovarian reserve is among the crucial long‐term side effects of using chemotherapy agents in breast cancer, yielding early ovarian failure. On the other hand, vitamin D is an essential factor in protecting the follicles and an important predictive factor for successful IVF therapy. Aim The aim of this study is evaluation of vitamin D as a agent that can reduce fertility complications of chemotherapy specially in young women. Methods Breast cancer patients undergoing chemotherapy at two cancer institutes were enrolled in this study. The case group received 1000 IU of calcitriol, and the AMH level was measured at the baseline, after chemotherapy, and six months after chemotherapy. The primary end point was improvement in the AMH level after six months of chemotherapy. the secondary endpoint was to evaluate the predictive factors of AMH level decline during chemotherapy. Results Between 2018 and 2019, 18 and 15 patients were enrolled in the case and control groups, respectively. The mean AMH level (ngr/ml) of the patients in the case and control group were 3.16 and 2.37 ng/mL, respectively (p‐value = .16). These levels were 0.387 and 0.19 after six months (p‐value = .38). The AMH rise immediately after chemotherapy cycles to six months after chemotherapy, in the case and control groups were 0.86 and 0.44 ng/mL, respectively, which was slightly higher in the case group but not statistically significant between two groups (p‐value = .054). Conclusion Despite a minimal rise in the AMH level after six months of chemotherapy, the study could not demonstrate any protective effect of vitamin D on patients' ovarian reserve undergoing chemotherapy for breast cancer. Further larger studies are needed to evaluate the effect of vitamin D supplements on ovarian reserve beside optimal dose and duration.